2018
DOI: 10.1021/acs.nanolett.8b03937
|View full text |Cite
|
Sign up to set email alerts
|

Strain-Tunable Quantum Integrated Photonics

Abstract: Semiconductor quantum dots are crucial parts of the photonic quantum technology toolbox because they show excellent single-photon emission properties in addition to their potential as solid-state qubits. Recently, there has been an increasing effort to deterministically integrate single semiconductor quantum dots into complex photonic circuits. Despite rapid progress in the field, it remains challenging to manipulate the optical properties of waveguide-integrated quantum emitters in a deterministic, reversible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 56 publications
2
57
1
Order By: Relevance
“…To address this issue, methods for tuning emitter properties are critical for generating identical photons, [ 3 ] and for coupling to high‐quality factor photonic resonators, where tuning magnitudes must be comparable to or greater than the cavity linewidths. [ 4 ]…”
Section: Figurementioning
confidence: 99%
“…To address this issue, methods for tuning emitter properties are critical for generating identical photons, [ 3 ] and for coupling to high‐quality factor photonic resonators, where tuning magnitudes must be comparable to or greater than the cavity linewidths. [ 4 ]…”
Section: Figurementioning
confidence: 99%
“…Another effective technique for the pick-and-place approach is using a sharp micro-probe [56, 101,102,110,111] In particular, the latter environment significantly improves the alignment accuracy over the transfer printing method. Additionally, using the probe tip, it is possible to change the emitter position for better alignment accuracy even after integration.…”
Section: Pick-and-placementioning
confidence: 99%
“…However, here a butt coupling method between the quantum emitters and SiN waveguide was used reducing the theoretical coupling efficiency from 37% to 1%. In further studies of the same group, it was shown that silicon nitride waveguides can be directly fabricated on a piezoelectric substrate (PMN‐PT) . This made the tuning of the emission energy via an applied strain field up to 1.6 nm feasible.…”
Section: Hybrid Quantum Photonic Circuitsmentioning
confidence: 99%